Suppression of non-albicans candida species (NAC) biofilm formation by probiotic Streptococcus salivarius - Soffian, Sharmeen Nellisa; Rismayuddin, Nurul Alia Risma; Mokhtar, Munirah; Arzmi, Mohd Hafiz (Fakulti Perubatan dan Sains Kesihatan, Universiti Putra Malaysia, 2019)
Introduction: Candida spp. are most common opportunistic pathogenic yeast that inhabit human oral cavity, epidermis, gastrointestinal tract, and vagina leading to candidiasis. The transition of this yeast from commensal to potent pathogen is facilitated by numbers of virulence factors including biofilm formation. While most reports on candidiasis are associated with formation Candida albicans biofilms, however, non-albicans Candida species prevalence is of growing concern. Recently, the use of probiotics as antifungal and antibiofilm has gained an increasing attention. As such, we aim to evaluate the inhibitory effect of monomicrobial and polymicrobial of Streptococcus Salivarius on six strains of NAC namely Candida dubliniensis, Candida glabrata, Candida krusei, Candida lusitanaei, Candida parapsilosis and Candida tropicalis. Methods: Antifungal activity of S. salivarius on NAC species was performed using well diffusion method on Mueller Hinton Agar (MHA) and the diameter of inhibition zone were assessed. For formation of monomicrobial biofilm, standardized cell suspensions of NAC species and probiotic Streptococcus salivarius were grown in RPMI or nutrient broth media at 37°C for 72 h. Meanwhile to study polymicrobial biofilm -of both NAC and 5. salivarius, similar protocol was employed by inoculating both microorganisms with a similar cell density as in monomicrobial. Finally, biofilrm formation was assessed through quantification of total biomass by crystal violet (CV) assay and the absorbance of adherent biofilm was measured in triplicate at 620nm. Results: Antifungal susceptibility testing of S. salivarius on all six NAC species discerned no zone of inhibition. Furthermore, our results showed variability of monomicrobial and polymicrobial biofilm biomass between NAC species and growth medium. All six polymicrobial NB-grown and RPMl-grown exhibited decreased of the biofilm formation. C. parapsilosis co-cultured with 5. salivarius in NB medium had shown lowest biofilm biomass by 75.51 + _1 .34% while in RPMI medium, C. lusitanaei demonstrated with most reduced biofilm biomass by 67.03+ _5. 19. Conclusion: Our study elucidated the antagonistic relationship between Streptococcus salivarius and non-albicans Candida by supressing the growth of polymicrobial biofilm and pseudohyphae/hyphae of NAC species.